On some fixed point theorems for asymptotically Quasi-Nonexpansive nonself mappings on banach spaces - Supamit Wiriyakulopast (Prince of Songkla University, 2013)
Thesis (M.Sc., Mathematics and Statistics)--Prince of Songkla University, 2012